2022
DOI: 10.20338/bjmb.v16i4.300
|View full text |Cite
|
Sign up to set email alerts
|

Quiet eye training alleviates the yips in golf putting: a research proposal

Abstract: A case study is presented of a professional golfer (AB) who in her 13th LPGA season suffered from the psychological form of the YIPS. She had increased anxiety about her technique and eye movements that made focusing difficult. After a quiet eye (QE) training program she overcame the YIPS and had her 2nd best season. However, her improvement was temporary for reasons that may have been due to how the treatment was delivered. Due to the pandemic, she was given a QE training program that used email, phone calls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Prolonging the quiet eye period can reduce the adverse effects of competition anxiety, and quiet eye training is of great significant in combating anxiety 8 10 . In research studies, it has been found that athletes improve their sports performance by adopting more effective attentional strategies 11 , 12 . Additionally, quiet eye training has been shown to reduce the negative impact of anxiety and competitive pressure on performance, to a certain extent 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonging the quiet eye period can reduce the adverse effects of competition anxiety, and quiet eye training is of great significant in combating anxiety 8 10 . In research studies, it has been found that athletes improve their sports performance by adopting more effective attentional strategies 11 , 12 . Additionally, quiet eye training has been shown to reduce the negative impact of anxiety and competitive pressure on performance, to a certain extent 13 .…”
Section: Introductionmentioning
confidence: 99%